1999
DOI: 10.1097/00000539-199905000-00006
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Intravenous Lactated Ringer’s Solution Versus 0.9% Sodium Chloride Solution on Serum Osmolality in Human Volunteers

Abstract: Large volumes of lactated Ringer's solution administered to healthy humans produced small transient changes in serum osmolality. Large volumes of sodium chloride did not change osmolality but resulted in lower pH.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
214
0
13

Year Published

2005
2005
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 239 publications
(241 citation statements)
references
References 14 publications
9
214
0
13
Order By: Relevance
“…Inclusion and exclusion criteria were evaluated by an independent physician prior to study start, and deferred written informed consent was obtained from a close family member within 48 h after admission to the intensive care unit. A previous study including 36 volunteers assigned to saline versus balanced infusion reported significant differences in pH, serum osmolality, and sodium concentration [11]. Accordingly, we aimed to include 18 patients per group.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Inclusion and exclusion criteria were evaluated by an independent physician prior to study start, and deferred written informed consent was obtained from a close family member within 48 h after admission to the intensive care unit. A previous study including 36 volunteers assigned to saline versus balanced infusion reported significant differences in pH, serum osmolality, and sodium concentration [11]. Accordingly, we aimed to include 18 patients per group.…”
Section: Methodsmentioning
confidence: 99%
“…Nevertheless, this has never been shown in patients after SAH. In addition, normal saline has been associated with metabolic acidosis and slower urinary output in volunteers [11] and with metabolic acidosis and hyperkalemia in patients undergoing kidney transplantation [12] compared with lactated Ringer's solutions. On the other hand, balanced IV solutions were able to prevent the development of hyperchloremic metabolic acidosis, and provided better gastric mucosal perfusion compared with saline-based fluids in elderly surgical patients [13].…”
Section: Introductionmentioning
confidence: 99%
“…Studies in healthy volunteers and patients undergoing major surgery have demonstrated significant hyperchloraemia following administration of 0.9% sodium chloride, leading to hyperchloraemic metabolic acidosis, an increased incidence of postoperative nausea and vomiting and a temporary reduction in the glomerular filtration rate. [6][7][8] It is estimated that in healthy volunteers it can take up to two days to excrete a rapid infusion of two litres of 0.9% sodium chloride solution; 9 in hospital inpatients administered IV fluids for prolonged periods of time, this can increase the risk of fluid overload and associated complications. Studies in surgical patients have shown that the use of 0.9% sodium chloride solution compared to balanced fluid solutions is associated with an increased in-hospital mortality (5.6% compared to 2.9%, p<0.001).…”
Section: Introductionmentioning
confidence: 99%
“…The infusion of NS has also been recognized as the reason for complications such as mental changes and abdominal discomfort in healthy volunteers. [9] While several studies have shown evidence indicating LR as a safe alternate for NS due to a lower risk of hyperkalemia, NS is still the most commonly used fluid in many centers. Thus, investigations in this area could result in meaningful practical changes.…”
Section: Introductionmentioning
confidence: 99%